Observations of a narrow zone of high suspended particulate matter (SPM) concentrations along the Dutch coast. (1st March 2015) - van der Hout, Carola M.; Gerkema, Theo; Nauw, Janine J.; Ridderinkhof, Herman
Abstract: The objective of the study described in this paper is to localize the transport path of suspended particulate matter (SPM) in the Dutch coastal zone in the southern North Sea. It is known that a large mass of SPM is transported northward from the Strait of Dover, which is however mostly hidden from satellite and other surface measurements. The study area is located at 80 km north of the Rhine-Meuse estuary mouth in the far-field plume of the region of freshwater influence (ROFI). We investigate the occurrence and persistence of a turbidity maximum zone (TMZ) in an area closer to the coast than studied in previous observational programs. Shipboard measurements of vertical profiles of SPM concentrations, density and current velocities with a high cross-shore spatial resolution are presented. A turbidity maximum zone is found at a distance between 0.5 and 3 km from the coast along 30 km of the coastline. Observed concentrations are shown to vary strongly within a tidal cycle, and also between contrasting meteorological conditions in terms of the spring-neap tidal cycle, the significant wave height and the wind force. Temporary stratification is observed during spring tides, and occurs on the ebb phase of the tidal cycle. Cross-shore transports at a transect perpendicular to the coast show an accumulation of SPM in the TMZ within one tidal cycle. Possible mechanisms for this accumulation close to the coast are discussed. Highlights: SPM concentrations were measured in the far-field plume of the Rhine ROFI. A turbidity maximum zone (TMZ) is observed within 5 km from the coast. In the TMZ, cross-shore accumulation occurs during calm weather.